The Effect of Chinese Herbal Medicine on Quality of Life and Exercise Tolerance in Heart Failure With Preserved Ejection Fraction: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Wang, Jinping; Yang, Ran; Zhang, Feilong; Jia, Caixia; Wang, Peipei; Liu, Junjie; Gao, Kuo; Xie, Hua; Wang, Juan; Zhao, Huihui; Chen, Jianxin; Wang, Wei (Frontiers in Physiology, 2018)
Background: Chinese herbal medicine (CHM) has a good effect of alleviating symptoms and improving quality of life and exercise tolerance in patients with heart failure with preserved ejection fraction (HFpEF), but it wasn’t sufficiently valued and promoted because of the lack of evidence-based medical evidence. Aim: To systematically review the effect of CHM on quality of life and exercise tolerance in patients with HFpEF. Methods: We conducted a systematic literature search for Chinese and English studies in PubMed, EMBASE, Cochrane Central Register of Controlled Trials, Chinese Biomedical Literature Database, China Knowledge Resource Integrated Database, Wanfang Data, and China Science and Technology Journal Database. Databases were searched using terms relating to or describing CHM, HFpEF and randomized controlled trials, without any exclusion criteria for other types of diseases or disorders. Literature retrieval, data extraction, and risk of bias assessments were performed independently by two investigators. Differences were resolved by consensus. RevMan 5.3.0 was used for data analysis. Quantitative synthesis was used when the included studies were sufficiently homogeneous and subgroup analyses were performed for studies with different sample sizes and blind methods. GRADEpro was used to grade the available evidence to minimize bias in our findings. Results: 17 studies with 2724 patients were enrolled in this review. ROB assessments showed a relatively high selection and performance bias. Meta-analyses showed that compared with conventional western medicine, combined CHM and conventional western medicine could significantly improve 6-minute walk distance (MD = 52.13, 95% CI [46.91, 57.34], P < 0.00001), and it seemed to be more effective as compared with combined placebo and conventional western medicine. Similar results were observed for quality of life and the results were better in a larger sample. The GRADEpro showed a very low to moderate level of the available evidence. Conclusion: Combined CHM and conventional western medicine might be effective to improve exercise tolerance and quality of life in HFpEF patients, but new well-designed studies with larger sample size, strict randomization, and clear description about detection and reporting processes are needed to further strengthen this evidence.